Environmental Policies and Stagnation in a Two-Country Economy - Masako Ikefuji; Yoshiyasu Ono (Center for Economic Studies and ifo Institute (CESifo), 2023)
Global warming is a serious and acute threat to our planet, but, when negotiating the allocation of permissible carbon emissions, conflicts of interest exist between developed and developing countries. Developing countries insist that global warming is the result of prolonged pollution emissions by developed countries, while developed countries demand that developing countries make efforts comparable to their own to reduce carbon emissions. They both generally believe that stricter emission limits will burden their economies because of the extra abatement costs required. We use a two-country model with wealth preferences and find that the effects of a country's emission limit on the two countries' real consumption and pollution emissions differ, depending on the combination of their business situations. If both countries achieve full employment, one country's stricter emission limit decreases both countries' real consumption, as expected. However, if one country faces aggregate demand stagnation and the other achieves full employment, a stricter emission limit imposed by the stagnant country increases both countries' real consumption.
Keywords: F13; F41; F42; Q52; Q56; Q58; 330; persistent unemployment; wealth preferences; pollution; emission restriction; clean technology transfer